2017
DOI: 10.7554/elife.24560
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of an intricate J-protein network driving protein disaggregation in eukaryotes

Abstract: Hsp70 participates in a broad spectrum of protein folding processes extending from nascent chain folding to protein disaggregation. This versatility in function is achieved through a diverse family of J-protein cochaperones that select substrates for Hsp70. Substrate selection is further tuned by transient complexation between different classes of J-proteins, which expands the range of protein aggregates targeted by metazoan Hsp70 for disaggregation. We assessed the prevalence and evolutionary conservation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 81 publications
2
92
0
2
Order By: Relevance
“…How these states contribute to Hsp70 function is currently not clear. Also, as mentioned above class A and class B JDPs form complexes in vitro and in vivo boosting Hsp70 disaggregation activity (89,90,120). Because both class A and class B JDPs are dimers, potentially four J-domains are available for interacting with Hsp70s and could target several Hsp70s simultaneously to bind to aggregates in close proximity to each other.…”
Section: Current Questionsmentioning
confidence: 91%
See 1 more Smart Citation
“…How these states contribute to Hsp70 function is currently not clear. Also, as mentioned above class A and class B JDPs form complexes in vitro and in vivo boosting Hsp70 disaggregation activity (89,90,120). Because both class A and class B JDPs are dimers, potentially four J-domains are available for interacting with Hsp70s and could target several Hsp70s simultaneously to bind to aggregates in close proximity to each other.…”
Section: Current Questionsmentioning
confidence: 91%
“…Recently, it was shown that some class A and class B JDPs cooperate in protein disaggregation. This cooperation involves not only a division of labor with DNAJA2 preferentially targeting small aggregates and DNAJB1 large aggregates but even more a direct interaction between the class A and the class B JDP, suggesting the formation of a high order complex with Hsp70s (89,90).…”
Section: J-domain Proteins: Hsp70 Targeting Factorsmentioning
confidence: 99%
“…The major de novo protein folding chaperones in eukaryotes are Hsp90 and Hsp70. These ATP‐dependent chaperones appear as constitutively expressed and stress‐induced forms and team up with various cochaperones for substrate recognition, binding, and activation . Hsp70 and Hsp90 chaperone systems play a role in different organelles of the eukaryotic cell and regulate a wide range of events including folding of de novo synthesized polypeptides, refolding, or degradation of misfolded proteins.…”
Section: The Chaperone Networkmentioning
confidence: 99%
“…These classical Hsp40 members assemble into homo-dimers through conserved C-terminal motifs and bind unfolded substrates through conserved β -barrel C-terminal domains (CTD) 20 . Recent evidence suggests that this subset of Hsp40s can form mixed hetero-dimers driven by electrostatic contacts to expand the substrate recognition repertoire 21 .…”
Section: Introductionmentioning
confidence: 99%